Sosialisasi Serta Memasyarakatkan Kembali Olahraga Tradisional ( Sreng ) Di Sma Negeri 1 Bergas - Wawan Agus Budiawan (edujavare, 2025)
In general, researchers can say that the implementation of community service at SMA Negeri 1 Bergas with the theme Socialization of Sreng Traditional Sports as a Regional Asset has been quite effective from the preparation stage to implementation. The enthusiasm, response and support from the school for this activity was enormous, starting from the Principal as leader, the teacher council involved to the students at SMA Negeri 1 Bergas. The re-introduction of the traditional sreng game presented by the researcher was accepted by the participants as a very enjoyable activity, so that when the session was well implemented the material delivery session and the practice of the traditional game ran smoothly. The results that researchers can convey regarding this activity are very effective and have an impact, especially on students in the Bergas 1 Public High School environment. Previously it was rare to see students playing traditional games during recess or when there were no lessons, but now you can find some students starting to preserve it by playing traditional games in the school environment without feeling awkward.